A Review of Accelerometer-based Activity Monitoring in Cancer Survivorship Research. Issue 9 (September 2018) - PEDDLE-MCINTYRE, CAROLYN J.; CAVALHERI, VINICIUS; BOYLE, TERRY; MCVEIGH, JOANNE A.; JEFFERY, EMILY; LYNCH, BRIGID M.; VALLANCE, JEFF K.
ABSTRACT: Background: In the cancer survivorship context, physical activity and sedentary behavior have been measured using different methods. Purpose: To conduct a narrative review of published research in cancer survivor populations to summarize the quality and identify gaps in reporting on accelerometer data collection, data processing, and outcome measures in cancer survivors. Methods: An initial PubMed® search of articles published in English was conducted in January 2017, and a final search was conducted in May 2017. Variables extracted included study characteristics, methods for accelerometry data collection (e.g., device used), data processing (e.g., cut points used), and data reporting (e.g., time spent in different activity intensities). Results: A total of 46 articles were eligible for inclusion in the review. The majority of studies (34 of 46) targeted a single cancer group and 18 of these 34 studies were in survivors of breast cancer. Half (54%) of the studies used an ActiGraph® accelerometer. Methods of accelerometer data processing varied across studies. Definitions of non–wear time, vectors used during processing, and filters applied during processing were reported by 51%, 60%, and 8% of studies, respectively. Most studies reported moderate and vigorous physical activity (78%), 50% reported sedentary time, and 43% reported light-intensity activity. Cut points to categorize these activities varied between studies. Conclusions: This narrative review highlights inconsistency in the methods used to collect, process, and report accelerometry data across cancer survivor studies. Accelerometry has potential to add detailed knowledge of the levels and patterns of physical activities and sedentary behaviors across the cancer spectrum. Recommendations are made to improve data processing and reporting methods to maximize the scientific validity of future accelerometer research in this field. Abstract : Supplemental digital content is available in the text.